2016
DOI: 10.3329/mediscope.v3i1.29730
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing pattern in cesarean section

Abstract: Use of antimicrobials in caesarean section has become an accepted practice to minimize the incidence of postoperative complications. Not many studies are available in Bangladesh regarding the using pattern of antibiotics in caesarean section. The objectives of the study was to find out the pattern of use of antibiotic prophylaxis in caesarean section and also the frequency of postoperative morbidity. The prospective cross-sectional study included 356 patients undergoing caesarean section in Prime Medical Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…In the current study, it was noted that the majority of women who delivered through CS were in the age group between 21 and 25 years and above, which was in agreement with several similar studies [12] [28] [29] [30]. In our study, the most commonly prescribed antibiotics were the combination of benzylpenicillin, gentamicin and metronidazole or cefotaxime.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, it was noted that the majority of women who delivered through CS were in the age group between 21 and 25 years and above, which was in agreement with several similar studies [12] [28] [29] [30]. In our study, the most commonly prescribed antibiotics were the combination of benzylpenicillin, gentamicin and metronidazole or cefotaxime.…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated that 56% of women who underwent CS delivery were from low-cost residential areas, similar to other studies [12] [28] [31]. It was also determined that all the patients who had CS delivery received perioperative anti-biotic prophylaxis and anaesthetic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation